Atrial fibrillation and flutter – the state of the art. Part 2 - Janion-Sadowska, Agnieszka; Turek, Łukasz; Dudek, Aneta; Andrychowski, Jarosław; Sadowski, Marcin (Medical Studies/Studia Medyczne, 2021)
Despite constantly updating our knowledge on atrial fibrillation and flutter there are many questions and doubts about the nature and extent of arrhythmic and non-arrhythmic consequences of these arrhythmias. In part 1 of the state-of-the-art paper the diagnostic work-up of patients with the 2 arrhythmias was summarized. The management of patients with atrial fibrillation and flutter requires a multidisciplinary approach in the risk assessment (including stroke) and treatment strategy. Regardless of the type of antiarrhythmic or anticoagulant therapy, benefits must always surpass or at least offset potential adverse effects and drug toxicity. In part 2 of the state-of-the-art paper, current therapeutic strategies have been summarized.